Bernal & Florinda a Spanish tale - Kimmel, Eric 1946- (Holiday House, 1994)
An original story written in the tradition of the Spanish picaresque tale, tells of a clever but poor cavalier who wins the hand of his true love by outwitting her father, the wealthy mayor of Seville